A survey of Sydney general practitioners' management of patients with chronic hepatitis B. Issue 2 (1st February 2016) - Najjar, Zeina; Gupta, Leena; Pritchard‐Jones, Janice; Strasser, Simone I; Levy, Miriam T; Liaw, Siaw‐Teng; Cowie, Benjamin C
Abstract: Objective: To examine the chronic hepatitis B (CHB) assessment and management practices of general practitioners in the Sydney and South Western Sydney Local Health Districts, areas with a high prevalence of CHB, and to obtain their views on alternative models of care. Design, setting and participants: We used a descriptive, cross‐sectional study design to survey GPs who had seen at least one patient aged 18 years or over who had been notified as having CHB to the Public Health Unit between 1 June 2012 and 31 May 2013. There were 213 eligible GPs; the response rate was 57.7%. Main outcome measures: The CHB assessment, management and referral practices of the GPs, and their opinions about different models of care. Results: Most GPs (78.9%) were at least reasonably confident about managing CHB. GPs were generally most comfortable with a model of care that involved initial referral to a specialist; managing CHB without specialist input or with only review by a specialised nurse practitioner were less popular. Conclusion: These results suggest that barriers, including dependence on specialist input, still hinder the appropriate assessment and management of CHB patients by GPs. Well designed and targeted support programs that include specialist support are needed if there is to be a successful shift to an increased role for GPs in the model of care for managing CHB.